Misi Gereja Dalam Krisis Ekologi - Sarimbangun, Ramli; Talumepa, Ventje Albert (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2025)
This article discusses the ecological crisis from a missiological perspective, highlighting the vital roleof the church as the holder and implementer of God's mandate, namely cultural and evangelicalmandates, in dealing with increasingly deepening environmental challenges. The research method usedin this paper is a qualitative method. For the purposes of exploring the data required, observation ofthe research location, interviews with respondents who were categorized according to the inherentcapacity of the respondents, and literature were used to look at theories and relevant documentation.The research findings are the lack of literacy among community members and churches regardingecology as the integrity of God's creation. Church leadership has an important role in environmentalpolicy advocacy, seeking to influence decision-making that supports sustainability and natureconservation. The novelty of this paper is a missiological perspective in the context of the ecologicalcrisis, which has not been widely explored in the literature, by emphasizing the role of the church inovercoming environmental challenges. In conclusion, the Church is a leader in creating collectiveawareness to overcome the ecological crisis, and ensure sustainable survival in the future.